Mapping the markets : a guide to stockmarket analysis - Owen, Deborah; Griffiths, Robin, 1943?- (London : Profile Books, 2006)
"This book is about how to analyze the way markets are likely to behave. It combines technical analysis, which is based on the belief that price reflects everything known about a particular market, and fundamental analysis, which takes into account an individual company's sales, earnings, and the value of its assets"--Provided by publisher.
Economic cycles -- Stockmarket cycles -- Sector rotation -- Stock selection -- Economic catch-up -- Demographic trends -- Energy -- Biotechnology -- Global imbalances -- External events -- Stockmarkets -- Sectors.
Includes bibliographical references (p. 124-127) and index.
Keywords: Stock exchanges; Business cycles; Investments